(untitled) (Società e diritti, 2022)
This paper analyses the issue of the effectiveness (ineffectiveness) of law in the light of Theodor Geiger’s reflections on the subject in his book Vorstudien zu einer Soziologie des Rechts (1947), in order to identify the variables that seem most likely to influence it.